The complex network of transcription factors, immune checkpoint inhibitors and stemness features in colorectal cancer: A recent update. (February 2023) - Merhi, Maysaloun; Ahmad, Fareed; Taib, Nassiba; Inchakalody, Varghese; Uddin, Shahab; Shablak, Alaaeldin; Dermime, Said
Abstract: Cancer immunity is regulated by several mechanisms that include co-stimulatory and/or co-inhibitory molecules known as immune checkpoints expressed by the immune cells. In colorectal cancer (CRC), CTLA-4, LAG3, TIM-3 and PD-1 are the major co-inhibitory checkpoints involved in tumor development and progression. On the other hand, the deregulation of transcription factors and cancer stem cells activity plays a major role in the development of drug resistance and in the spread of metastatic disease in CRC. In this review, we describe how the modulation of such transcription factors affects the response of CRC to therapies. We also focus on the role of cancer stem cells in tumor metastasis and chemoresistance and discuss both preclinical and clinical approaches for targeting stem cells to prevent their tumorigenic effect. Finally, we provide an update on the clinical applications of immune checkpoint inhibitors in CRC and discuss the regulatory effects of transcription factors on the expression of the immune inhibitory checkpoints with specific focus on the PD-1 and PD-L1 molecules. Graphical Abstract: ga1